2020
DOI: 10.1007/s40964-020-00152-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle size of monomodal 316L powder on powder layer density in powder bed fusion

Abstract: Powder layer density is an important measure for understanding the effect of powder on part quality in powder bed fusion. The density of thin layers, as they are deposited in powder bed fusion, differs from the density of powder in large containers. This study investigates this difference. Therefore, six monomodal powders with different particle size distributions, from coarse to fine, are spread in an 84.5 µm deep cavity to determine their powder layer densities for a single layer. A linear dependence of powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…The aspect ratio was lower than the circularity for all powders. The absolute values of the circularity and aspect ratio were within the range of what has been reported in the literature for the respective production processes [11,[25][26][27][28][29]. Furthermore, the results showed a strong correlation between powder circularity and aspect ratio with a Pearson correlation coefficient (PCC) of r (12) = 0.91, p < 0.001.…”
Section: Powder Processingsupporting
confidence: 78%
See 1 more Smart Citation
“…The aspect ratio was lower than the circularity for all powders. The absolute values of the circularity and aspect ratio were within the range of what has been reported in the literature for the respective production processes [11,[25][26][27][28][29]. Furthermore, the results showed a strong correlation between powder circularity and aspect ratio with a Pearson correlation coefficient (PCC) of r (12) = 0.91, p < 0.001.…”
Section: Powder Processingsupporting
confidence: 78%
“…For all powders, the PLD in the 84.5 µm cavity was lower than in the 141.4 µm cavity, and both PLDs were lower than the apparent density of the powders. This was due to the wall effect, which is the reduction of packing density through vacant sites in a packed powder in the presence of a wall, as discussed in [29,30]. For a solid material layer with a height of 30 µm, recent studies indicate that 141.1 µm is close to the realistic effective powder layer thickness for the LPBF process; Wischeropp et al [6] measured it to be between 130 and 165 µm.…”
Section: Powder Layer Density Tap Density and Apparent Densitymentioning
confidence: 99%
“…The profiler features a repeatability in the Z and X axes of 0.4 and 0.5 μm respectively, and a XY pixel size of 10 μm (set by the axis encoder) over a scanning length in the X direction of about 16 mm. Using a steel blade within the test bench, about 12 cubic centimeters of powder were deposited into the metal cavity with a circular shape, a nominal depth of 140 μm and a calculated volume of 177.71 mm 3 using the procedure developed by Haferkamp et al [ 15 ]. The goal of the cavity is to mimic the actual layer thickness of a powder bed fusion process, and in this specific case, an intuitive correlation between powder bed in a PBF machine and layer density in the test bench can be assumed.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Powder layer density is one of the metrics used in the literature [ 14 ] to study powder flowability and the associated influence on powder bed fusion processes. Haferkamp et al [ 15 ] demonstrated a lack of correlation between layer density and part quality with a wide range of 316L stainless steel powders characterized by different particle size, however the dynamics of the material-melt pool interactions in metal laser powder bed fusion is drastically different than when using polymer powder. Since preheating is applied in the case of polymer feedstock, the laser-matter interaction happens close to the powder melting point and hence, a reduced thermal shock for the feedstock leads to a more stable process.…”
Section: Introductionmentioning
confidence: 99%